Non-Toxic Increases in Nitrogen Availability Can Improve the Ability of the Soil Lichen Cladonia rangiferina to Cope with Environmental Changes - Lourdes Morillas; Javier Roales; Cristina Cruz; Silvana Munzi (Journal of Fungi, 2022)
Climate change and atmospheric nitrogen (N) deposition on drylands are greatly threatening these especially vulnerable areas. Soil biocrust-forming lichens in drylands can provide early indicators of these disturbances and play a pivotal role, as they contribute to key ecosystem services. In this study, we explored the effects of different long-term water availability regimes simulating climate changes and their interaction with N addition on the physiological response of the soil lichen Cladonia rangiferina. Three sets of this lichen were subjected to control, reduced watering, and reduced watering and N addition (40 kg NH4NO3 ha−1 year−1) treatments for 16 months. Finally, all samples were subjected to daily hydration cycles with N-enriched water at two levels (40 and 80 kg NH4NO3 ha−1 year−1) for 23 days. We found that reduced watering significantly decreased the vitality of this lichen, whereas N addition unexpectedly helped lichens subjected to reduced watering to cope with stress produced by high temperatures. We also found that long-term exposure to N addition contributed to the acclimation to higher N availability. Overall, our data suggest that the interactions between reduced watering and increased N supply and temperature have an important potential to reduce the physiological performance of this soil lichen.